Salt‐Induced High‐Density Vacancy‐Rich 2D MoS2 for Efficient Hydrogen Evolution - Man, Ping; Jiang, Shan; Leung, Ka Ho; Lai, Ka Hei; Guang, Zhiqiang; Chen, Honglin; Huang, Lingli; Chen, Tianren; Gao, Shan; Peng, Yung‐Kang; Lee, Chun‐Sing; Deng, Qingming; et al. (Advanced materials (Weinheim), 2024)
Emerging non‐noble metal 2D catalysts, such as molybdenum disulfide (MoS2), hold great promise in hydrogen evolution reactions. The sulfur vacancy is recognized as a key defect type that can activate the inert basal plane to improve the catalytic performance. Unfortunately, the method of introducing sulfur vacancies is limited and requires costly post‐treatment processes. Here, a novel salt‐assisted chemical vapor deposition (CVD) method is demonstrated for synthesizing ultrahigh‐density vacancy‐rich 2H‐MoS2, with a controllable sulfur vacancy density of up to 3.35 × 1014 cm−2. This approach involves a pre‐sprayed potassium chloridepromoter on the growth substrate. The generation of such defects is closely related to ion adsorption in the growth process, the unstable MoS2‐K‐H2O triggers the formation of sulfur vacancies during the subsequent transfer process, and it is more controllable and nondestructive when compared to traditional post‐treatment methods. The vacancy‐rich monolayer MoS2 exhibits exceptional catalytic activity based on the microcell measurements, with an overpotential of ≈158.8 mV (100 mA cm−2) and a Tafel slope of 54.3 mV dec−1 in 0.5 m H2SO4 electrolyte. These results indicate a promising opportunity for modulating sulfur vacancy defects in MoS2 using salt‐assisted CVD growth. This approach represents a significant leap toward achieving better control over the catalytic performances of 2D materials. Sulfur vacancy engineering is a vital strategy to activate the hydrogen evolution activity of the MoS2 basal plane. Unlike traditional costly post‐treatment methods, this work demonstrates a novel salt‐assisted chemical vapor deposition method for synthesizing vacancy‐rich 2H‐MoS2 electrocatalysts with exceptional catalytic activity. The generation of such defects is closely related to ion adsorption in the growth process.